2013
DOI: 10.3389/fmicb.2013.00096
|View full text |Cite
|
Sign up to set email alerts
|

A brief multi-disciplinary review on antimicrobial resistance in medicine and its linkage to the global environmental microbiota

Abstract: The discovery and introduction of antimicrobial agents to clinical medicine was one of the greatest medical triumphs of the 20th century that revolutionized the treatment of bacterial infections. However, the gradual emergence of populations of antimicrobial-resistant pathogenic bacteria resulting from use, misuse, and abuse of antimicrobials has today become a major global health concern. Antimicrobial resistance (AMR) genes have been suggested to originate from environmental bacteria, as clinically relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
211
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(231 citation statements)
references
References 168 publications
(187 reference statements)
1
211
0
9
Order By: Relevance
“…Moreover, various studies have demonstrated that wastewater and animal waste contain large numbers of resistant bacteria, which can pass through the wastewater treatment plant (WWTP) and reach the receiving water bodies (Teuber, 2001;Kü mmerer, 2004;Jury et al, 2011;Rizzo et al, 2013;Zurfluh et al, 2013). There is growing concern that continuous discharge of these contaminants may, at least locally, lead to an increase in the natural resistance background levels and thus enhance the likelihood of antibiotic-resistance genes (ARGs) being transferred back to human and animal commensals or even pathogens (Kim and Aga, 2007;Martinez, 2009b;Cantas et al, 2013). In the long term, this 'environmental loop' could contribute to the spread of resistance in pathogens and undermine the effectiveness of current and future antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various studies have demonstrated that wastewater and animal waste contain large numbers of resistant bacteria, which can pass through the wastewater treatment plant (WWTP) and reach the receiving water bodies (Teuber, 2001;Kü mmerer, 2004;Jury et al, 2011;Rizzo et al, 2013;Zurfluh et al, 2013). There is growing concern that continuous discharge of these contaminants may, at least locally, lead to an increase in the natural resistance background levels and thus enhance the likelihood of antibiotic-resistance genes (ARGs) being transferred back to human and animal commensals or even pathogens (Kim and Aga, 2007;Martinez, 2009b;Cantas et al, 2013). In the long term, this 'environmental loop' could contribute to the spread of resistance in pathogens and undermine the effectiveness of current and future antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…In the present 21 st century every known pathogen is resistant to one or more antimicrobials. 1 Antibiotic medications are over used in both developed and developing countries. Indiscriminate use of drugs is an important global threat.…”
Section: Introductionmentioning
confidence: 99%
“…5 Now-a-days in appropriate prescribing of antibiotics in RTIs has become a common malpractice by many prescribers. 6,7 This practice further magnifies the emergence of antibiotic-resistant bacterial strains in addition to increased adverse effect, treatment cost, resource use and consultation with doctors.…”
Section: Introductionmentioning
confidence: 99%